Study of Satisfaction towards the Food Services in the PPLP and SKO Athlete Dormitories in Indonesia - Penggalih, Mirza Hapsari Sakti Titis; Sofro, Zaenal Mutaqqien; Laksono Trisnantoro; Edi Nurinda Susila; Ernawaty; Bayu Rahadian; Margono; Dadi Sujadi; Raden Isnanta; Hardiyanti, Marina; Nia Bactiar; Ghany, Remaydhina Mahsa Alvita (Media Gizi Indonesia, 2023)
Providing food for athletes is a special institutional arrangement that caters to athletes' specific needs. Athletes have different nutritional requirements than the non-athlete population, as they need more nutrients to compensate for the energy expended during training, competitions, and recovery after matches. Additionally, athletes must focus on fluid intake and sufficient nutrients to support post-training recovery for optimal performance. Therefore, meeting the needs and satisfaction of athletes becomes a crucial goal for athlete food service. Satisfaction can be assessed based on various indicators such as variety of menu and ingredients, suitable portion size, taste, serving time, packaging, and food handler hygiene. This study aims to assess athletes' satisfaction with the food service in athlete dormitories. The research is an observational survey with a cross-sectional approach involving 159 athletes aged 13-19 years from PPLP West Java, PPLP DIY, PPLP NTB, and SKO Cibubur. Data collection took place in May and July 2022. The research instrument used was a customer satisfaction survey questionnaire with a Likert scale ranging from 1 to 4, where one indicates 'very poor' and four indicates 'excellent.' The analysis technique used Pearson correlation in SPSS 16.0 software. The research showed a relationship between menu variety, ingredient variety, suitable portion size, serving time accuracy, food packaging, serving area, food handler hygiene, food presentation, and food taste with athletes' satisfaction level. Serving time accuracy, food packaging, hygiene, cleanliness of the serving area, food handler hygiene, food appearance, and taste correlate strongly with satisfaction.